Perubahan Kesenjangan Upah Antar Gender Terkait Pandemi Covid-19 di Indonesia - Meylan Ratnawati Panjaitan (BESTARI BPS Kalimantan Timur, 2023)
Gender inequality motivated by social and cultural factors is seemingly responsible for the wage inequality of male and female workers in Indonesia. This study uses SAKERNAS 2019-2021 data to investigate the employment condition and the wage gap across genders before and during the Covid-19 pandemic by employing OLS to examine the wage determinants and Blinder-Oaxaca to decompose the wage gap. The result of the study reports that male workers are waged 38 percent higher than female workers in 2019, and the wage gap decreased to 35.7 percent and 35.2 percent, respectively, in 2020 and 2021. However, further analysis with t-tests and z-test on wage gap comparisons among business sectors and provinces find no evidence that the wage gap across genders changes significantly due to the Covid-19 pandemic.